Koperasi Siswazah Bangi Berhad (KSBB) / Nur Afiqah Uzma Junaidy - Junaidy, Nur Afiqah Uzma (2021)
This internship report was submitted as part of the Bachelor degree of Information System Management requirements. Koperasi Siswazah Bangi Berhad (KSBB) was where I did my internship. The primary objective of this internship is to learn and apply what I learned at university, which was mostly theoretical. During my five-month internship, I was assigned to the Digital Marketing department. I was also given the task with interacting with clients from various backgrounds. While I was given the opportunity to complete my internship, I learned how to approach people, enter data, and improve my editing skills. There were a few hurdles that I had to overcome in the time allotted, but I was able to handle without difficulty. Several numbers or activities that were given including the special project. There will be four chapters that going to conclude the whole journey of my internship starting from the KSBB’s background to analysing and recommending the company. In conclusion, this was an immense opportunity for me to develop and improve my skills in my career field, which I did during the internship period.